Simultaneous microalgal biomass production and CO2 fixation by cultivating Chlorella sp. GD with aquaculture wastewater and boiler flue gas. (December 2016) - Kuo, Chiu-Mei; Jian, Jhong-Fu; Lin, Tsung-Hsien; Chang, Yu-Bin; Wan, Xin-Hua; Lai, Jinn-Tsyy; Chang, Jo-Shu; Lin, Chih-Sheng
Graphical abstract: Highlights: Combined aquaculture wastewater and flue gas was applied for Chlorella sp. culture. Microalgal cultivation was used to reuse water resource and reduce CO2 emission. Aquaculture wastewater with nutrient addition was suitable for Chlorella sp. culture. Biomass productivity of Chlorella sp. aerated with boiler flue gas was 1.296 g L −1 d −1 . CO2 fixation of Chlorella sp. aerated with boiler flue gas was 2.333 g L −1 d −1 . Abstract: A microalgal strain, Chlorella sp. GD, cultivated in aquaculture wastewater (AW) aerated with boiler flue gas, was investigated. When AW from a grouper fish farm was supplemented with additional nutrients, the microalgal biomass productivity after 7 days of culture was 0.794 g L −1 d −1 . CO2 fixation efficiencies of the microalgal strains aerated with 0.05, 0.1, 0.2, and 0.3 vvm of boiler flue gas (containing approximately 8% CO2 ) were 53, 51, 38, and 30%, respectively. When the microalgal strain was cultured with boiler flue gas in nutrient-added AW, biomass productivity increased to 0.892 g L −1 d −1 . In semi-continuous cultures, average biomass productivities of the microalgal strain in 2-day, 3-day, and 4-day replacement cultures were 1.296, 0.985, and 0.944 g L −1 d −1, respectively. These results demonstrate the potential of using Chlorella sp. GD cultivations in AW aerated with boiler flue gas for reusing water resources, reducing CO2 emission, and producing microalgal biomass.